Sources of unsafe primary care for older adults: a mixed-methods analysis of patient safety incident reports - Cooper, Alison; Edwards, Adrian; Williams, Huw; Evans, Huw P.; Avery, Anthony; Hibbert, Peter; Makeham, Meredith; Sheikh, Aziz; Donaldson, Liam J.; Carson-Stevens, Andrew (Oxford University Press, 2017)
Background: Older adults are frequent users of primary healthcare services, but are at increased risk of healthcare-related harm in this setting.